“Worse but Ours,” or “Better but Theirs?” – The Role of Implicit Consumer Ethnocentrism (ICE) in Product Preference - Maison, Dominika; Maliszewski, Norbert (Frontiers in Psychology, 2016)
The goal of this project was to investigate whether consumer ethnocentrism is purely conscious mechanism based on ideology, as suggested by Shimp and Sharma (1987), or rather is an automatic, unconscious process. The aim of the project was an introduction of the Implicit Consumer Ethnocentrism (ICE) concept, measured by the Implicit Association Test (IAT). The goal of the four studies conducted was to investigate the following issues: (a) whether ICE – an automatic mechanism underlying the preference for local products over foreign – this could be observed next to the more ideologically based classic consumer ethnocentrism; (b) what happens when the consumer’s automatic preference for local products (ICE) is confronted by objective evidence of the superiority of foreign products or by the inferiority of local products. It was assumed that Implicit Consumer Ethnocentrism could be reduced when foreign products were associated with a higher level of competence than local products, and this could explain the preference for foreign products over local often observed in less developed countries. In study 1 the ICE for different product categories of existing brands was tested, and in study 2 the ICE was measured in the context of nonexistent brands. Both studies showed a strong in-group brand preference and confirmed the existence of new phenomena – Implicit Consumer Ethnocentrism. The results of study 3 and 4 again indicated a strong, automatic in-group brand favoritism effect as measured by IAT – participants preferred local brands over foreign. However, the inclusion of well-known foreign brands associated with high competence reduced the IAT effect (in-group preference).